Soupy leaves home - Castellucci, Cecil, 1969- (Dark Horse Books, 2021)
When Pearl runs away from her abusive father, she has nowhere to go--until she stumbles onto a disguise. Reborn as a boy named Soupy, she joins up with a hobo named Ramshackle and the two take a train-hopping journey across America that helps them both heal.